A Primeron Mineral Taxation - Baunsgaard, Thomas (IMF Working Papers; Working Paper, 2001)
The paper discusses options available to tax mineral extraction projects particularly in developing countries. A desirable government share of the economic rent generated from mineral extraction can be achieved through different tax and non-tax instruments. This gives some room to design a fiscal regime that will be attractive to investors while providing the government with a fair share of the economic rent. However, achieving this will require a careful assessment of the appropriate distribution of risk and reward between the investor and the government. Moreover, there is growing pressure on countries to provide increasingly lenient fiscal terms so as to remain competitive as global investment destinations.